Social capital as a moderator of the relationship between violent community environment and psychological distress - Miguel A. Pérez-Sastré; Carmen García-Peña; Luciana Ramos-Lira; Luis Ortiz-Hernández (Elsevier, 2024)
Objective: To evaluate the modifying effect of social capital on the relationship between living in violent communities and the presence of psychological distress in adolescents and youth in Mexico. Method: The analysis of the Social Cohesion Survey for the Prevention of Violence and Crime (ECOPRED, by its acronym in Spanish) was conducted. The analytic sample consisted of 39,639 participants aged 12 to 29 years. Community violence and social capital were measured at the census tract level using the average answers of a household's head sample. These environmental variables were independent of the experiences of the participants. Social capital variables included structural (social ties, recreational participation, collaborative participation, and social cohesion), and cognitive (trust in neighbors) dimensions. Multilevel structural equation models were used. Results: Recreational participation, collaborative participation, and social cohesion modified the relationship between community environments and psychological distress. In females who lived in places with less recreational participation or less social cohesion, the higher the social disorder, the higher the psychological distress. A similar relationship between vandalism and psychological distress was identified, but only in males who lived in places with less collaborative participation, and in females with less social cohesion. Conclusions: Our results suggest that dimensions of the structural social capital (organization and interest in the community and its members) were the ones that had the buffering effect of the exposure to disordered community environments on psychological distress. Resumen: Objetivo: Evaluar el efecto modificador del capital social en la relación entre vivir en comunidades violentas y la presencia de distrés psicológico en adolescentes y jóvenes de México. Método: Se realizó un análisis de la Encuesta de Cohesión Social para la Prevención de la Violencia y el Delito (ECOPRED). La muestra analítica la conformaron 39.639 participantes de 12 a 29 años. La violencia comunitaria y el capital social se midieron por zonas censales utilizando el promedio de respuestas de una muestra de jefes de hogar. Estas variables ambientales fueron independientes de las experiencias de los participantes. Las variables del capital social incluyeron dimensiones estructurales (vínculos sociales, participación recreativa, participación colaborativa y cohesión social) y cognitivas (confianza en vecinos). Se utilizaron modelos de ecuaciones estructurales multinivel. Resultados: La participación recreativa, la participación colaborativa y la cohesión social modificaron la relación entre los ambientes comunitarios y el distrés psicológico. En las mujeres que se encontraban en lugares con menor participación recreativa o menor cohesión social, cuanto mayor era el desorden social, mayor era el distrés psicológico. Se identificó una relación similar entre vandalismo y distrés psicológico, pero solo en hombres que vivían en lugares con menor participación colaborativa y en mujeres con menor cohesión social. Conclusiones: Nuestros resultados sugieren que las dimensiones del capital social estructural (organización e interés en la comunidad y sus miembros) tienen un efecto amortiguador de la exposición a ambientes comunitarios desordenados sobre el distrés psicológico.